1980
DOI: 10.1063/1.328248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth conditions on tin incorporation in GaAs grown by molecular beam epitaxy

Abstract: Intentional perturbations applied to the growth parameters of Sn-doped GaAs layers grown by molecular beam epitaxy have been performed in order to investigate the tin incorporation mechanism. The start, the interruption, and the end of growth as well as a variation of fluxes or substrate temperature have been studied, using either the Auger electron spectroscopy (AES) measurement of tin accumulation on the surface, or C-V derived free-carrier concentration profile versus any of these growth parameters. The the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, the fact that such behavior is observed is not a guarantee that the incorporation is uniform in the grown layer, as is attested to by the fact that a linear dependence is also seen for Sn incorporation into GaAs, 5 where surface accunmlation during MBE is known to occur. 6,7 For the studies reported here, hcterostructures consisting oflayers of both InP and Gao.47Ino.53As lattice matched to InP were grown by HSMBE on (100) InP wafers. In the HSMBE version of gas source MBE (GSMBE) 8 the group V elemental molecular beams (As 2 and P 2) are derived from thermally decomposed AsH 3 and PH 3 while all other beams, induding the SIl beam, result from heating the elements in effusion cells.…”
mentioning
confidence: 99%
“…However, the fact that such behavior is observed is not a guarantee that the incorporation is uniform in the grown layer, as is attested to by the fact that a linear dependence is also seen for Sn incorporation into GaAs, 5 where surface accunmlation during MBE is known to occur. 6,7 For the studies reported here, hcterostructures consisting oflayers of both InP and Gao.47Ino.53As lattice matched to InP were grown by HSMBE on (100) InP wafers. In the HSMBE version of gas source MBE (GSMBE) 8 the group V elemental molecular beams (As 2 and P 2) are derived from thermally decomposed AsH 3 and PH 3 while all other beams, induding the SIl beam, result from heating the elements in effusion cells.…”
mentioning
confidence: 99%
“…They obtained smooth surface layers for binary compounds GaAs and AlAs, and the roughness was found to be maximal for the ternary compound Ga 0.5 Al 0.5 As. It was believed that the consequence would be a reduced ability of Al atoms to find the right incorporation sites before subsequent Al atoms arrive, favoring local inhomogeneity of the Al content of the layer [12]. Also, it could be thought that roughening would intensify as the number of foreign atom in the host lattice increases.…”
Section: Resultsmentioning
confidence: 98%
“…It was originally suggested (Cho 1975, Ploog andFischer 1978) that the tin was segregating to the surface of the growing film, but subsequently Wood and Joyce (1978) proposed a surface rate limiting process in which the Sn is incorporated from a surface layer, not directly from the vapour phase. This model has been extended by Alexandre et al (1980) and Wood et a1 (1980) and m is the order of the incorporation process. Because the surface Sn has a tendency to form three-dimensional islands an apparent zeroth-order behaviour with respect to Jsn can also be observed (Harris et a1 1982).…”
Section: Sn Doping Of Gaasmentioning
confidence: 99%